Caribbean Insular Mobilities - Carlo Cubero (Suomen Antropologi)
The article examines the role that processes suggestive of ‘mobility’ and ‘insularity’ have played in research that has concerned itself with the constitution of Caribbean island identities. Historically, the relationship between these two concepts has suggested a contradiction or a paradox to unravel. Here, the author reviews core concepts in Caribbeanist research and places ‘mobility’ and ‘insularity’ in conversation with each other, arguing that, rather than posing a puzzle to unravel, they operate simultaneously in the process of constituting Caribbean island social identities. Engaging with the simultaneity of stasis and movement can be a powerful tool for researchers seeking to understand the complexities of Caribbean social life.